Association of Bidara Leaf Tea (Ziziphus mauritiana) and Lemon (Citrus limon) Consumption with Changes in Creatinine Levels among Farmers Exposed to Heat Stress in Banyumas Regency - Nurul Amaliyah; Suparmin; Nur Hilal; Yulia (Jurnal Higiene Sanitasi, 2026)
Exposure to heat stress in agricultural work environments can increase the risk of dehydration and impaired kidney function. One commonly used indicator for assessing kidney function is serum creatinine levels. Bidara leaves (Ziziphus mauritiana) and lemon (Citrus limon) are known to contain antioxidant compounds that may help reduce oxidative stress and support kidney health. However, scientific evidence regarding the effects of a combination of these two ingredients on kidney function in humans remains limited. This study aimed to analyse changes in serum creatinine levels following the administration of a combination of bidara leaf and lemon tea to farmers exposed to heat stress in Banyumas Regency. The study employed a quasi-experimental design with aone-group pretest-posttest design. A total of 15 farmers were selected as participants using purposive sampling. The intervention consisted of a combination of bidara leaf tea and lemon, 200 mL of which was consumed three times a day for 14 consecutive days. Serum creatinine levels were measured before and after the intervention and analysed using the Wilcoxon Signed-Rank test. The results showed that the mean creatinine level decreased from 0.89 mg/dL before the intervention to 0.72 mg/dL after the intervention. Statistical analysis revealed a significant difference between creatinine levels before and after the intervention (p = 0.012). These findings suggest a link between the consumption of a combination of bidara leaf tea and lemon and a reduction in serum creatinine levels among farmers exposed to heat stress. However, the study results should be interpreted with caution given the absence of a control group, the small sample size, and the limited range of renal function parameters measured.